Learning Styles and Cognitive Styles of Prospective Mathematics Teachers in Matrix Algebra Courses - Irmawati Liliana Kusuma Dewi; Zaenuri Zaenuri; Dwijanto Dwijanto; Mulyono Mulyono (International Conference on Science, Education, and Technology, 2022)
In studying matrix algebra, prospective mathematics teachers must master, understand, and solve given problems. For prospective mathematics teachers to understand and solve the problems given, lecturers in teaching must pay attention to the learning and cognitive styles of prospective mathematics teachers. Because learning styles and cognitive styles are closely related to how the prospective mathematics teacher obtains, processes information and interacts in the classroom. The learning styles in question are visual, auditory and kinesthetic. Meanwhile, the cognitive styles discussed in this study are field-dependent (FD), field-neutral (FN), and field-independent (FI). This study aims to determine prospective mathematics teachers taking matrix algebra courses learning and cognitive styles. The research method used is descriptive qualitative, where data collection uses a learning style questionnaire and the Group Embedded Figure Test (GEFT). The population in this study were prospective mathematics teachers at Gunung Jati Swadaya University. The sample of this study was 23 prospective mathematics teachers who took matrix algebra courses. The results showed that prospective mathematics teachers had visual (V) 69%, auditory (A) 13%, kinesthetic (K) 17.4%, cognitive style FD 34.8%, FN 43.5%, and FI 21.7%. The combination of learning styles and cognitive results obtained is FD-V 21.7%, FN-V 34.8%, FI-V 13%, FD-A 4.3%, FN-A 4.3%, FI-A 4.3%, FD-K 8.7%, FN-K 4.3%, and FI-K 4.3%. Identifying learning and cognitive styles in the learning process is crucial so prospective mathematics teachers have a solid potential to manage their learning better.